Defect-driven selective metal oxidation at atomic scale - Qi Zhu (Nature Portfolio, 2021)
Crystal defects critically influence surface chemical reactions in nanomaterials, yet the basic mechanisms at play are still elusive. Here, the authors show the atomic-scale dynamics of surface oxidation at coherent planar defects in Ag and Pd, revealing how twins and stacking-faults selectively oxidize metallic nanocrystals.